Linguistic impressions on two axiomizations for Categorial Grammar - Pagani, Luiz Arthur (Proceedings of the Brazilian Symposium in Information and Human Language Technology (STIL); 2004: Proceedings of the 2nd Workshop in Information and Human Language Technology, 2004)
In the present essay, two different but logically equivalent axiomatizations of Categorial Grammar will be compared from an exclusively linguistic perspective: 1) the version of the so called reduction rules, and 2) the version of Lambek calculus. In order to do that, after a first section of introduction, each axiomatization will be separately presented in the second section. In the third section both versions will be commented in relation to the type of linguitic knowledge representation they allow. At the conclusion in the fourth section the reduction rules version is argued to be the best linguistic option. Although the observations are linguistically motivated, their conclusions affect the nature of the linguistic knowledge (especially the lexical one) to be represented in any parser for Categorial Grammar.